Embracing A New Era: The Urgent Education Transformation To Achieve The 2030 Sustainable Development Goals - Pramiasih, Endah; Yanto, Heri; Raharjo, Tri Joko (Universitas Negeri Semarang, 2024)
In order to reach the 2030 Sustainable Development Goals (SDGs), education must undergo a fundamental transformation in light of the new era of global dynamics, technological advancements, and climate change. The study looks at how urgent it is to change education in order to provide the next generation the knowledge and morals they need to create a prosperous and sustainable future. The report suggests changing the way that education is viewed, modernising pedagogies and curricula, enhancing the calibre of teachers, increasing access to inclusive education, fortifying funding and governance, and undertaking research to assist in this transition. In order to achieve the 2030 SDGs, the paper offers suggestions and advice for policies and programmes that would guarantee universal access to high-quality education, encourage inclusive and equitable education, and bolster education funding and governance.